IL-10 Expression-Inducing Gut Bacteria Alleviate High-Fat Diet-Induced Obesity and Hyperlipidemia in Mice - Kim, Hye-In; Yun, Soo-Won; Han, Myung Joo; Jang, Se-Eun; Kim, Dong Hyun (Journal of microbiology and biotechnology, 2020)
In the present study, we examined the effects of interleukin (IL)-10 expression-inducing bacteria HP1, HP2, and HP3 on high-fat diet (HFD)-induced obesity and liver steatosis in mice. Oral gavage of HP1, HP2, and HP3 reduced HFD-induced bodyweight gain, triglycerides, and total cholesterol levels in the blood and liver. They also suppressed HFD-induced colitis and the fecal δ,γ-Proteobacteria population. Of the tested bacteria, HP2, which most potently inhibited IL-10 expression, also suppressed HFD-induced bodyweight gain, liver steatosis, and colitis most effectively. These findings suggest that IL-10 expression-inducing gut bacteria can suppress obesity and liver steatosis.